Pengaruh Aromaterapi Lemon terhadap Penurunan Intensitas Nyeri Post Operasi Laparatomi di Ruang Bedah RSUD Raden Mataher Jambi - Hasyim Kadri; Salvita Fitrianti (Universitas Baiturrahim, 2020)
Laparatomi surgery in the Raden Mattaher Jambi Hospital Operating Room in the last 3 years has increased. The average per month of Laparatomi surgery in 2017 is 31 actions, in 2018 there are 33 actions and increased to 38 actions in 2019. This research aims to look at the effect of the aroma of lemon therapy on decreasing pain intensity in post-op Laparatomi patients in the operating room Raden Mattaher Hospital in Jambi. This research is a quantitative study with a pre-experimental design without control group. Aims to see the effect of the aroma of lemon therapy on the decrease in pain intensity in post-op Laparatomi patients in the Raden Mattaher Hospital Operating Room Jambi. The population of this study was all post-op patients in the Operating Room at Raden Mattaher Jambi Hospital in the 2019 Deesember period with a total of 44 people. Samples amounted to 10 people. Accidental sampling, t-dependent statistical test. The results of the study on average scale pain post Laparatomi patients before being given the aroma of lemon therapy was 5.20 (moderate pain). After being given the aroma of lemon therapy, the average pain scale of the patient was 4.50 (moderate pain). The difference between the pre-test and post-test pain scales was 0.70. There is an influence of the aroma of lemon therapy on the decrease in pain intensity in post-op Laparatomi patients with a p-value of 0.001 (p <0.05). Researchers hope at the Raden Mattaher Jambi Hospital to make the aroma of lemon therapy as an alternative that can be used to help reduce the pain felt by post-op Laparatomi patients.